Socio-Cultural Dynamics of Coastal Communities (Case Study; Management of Wood Crafts in Kilensari Village, Panarukan) - Dimas Imaniar; Erna Agustina (Journal of Aquaculture Science, 2021)
There is no society that does not experience change. Likewise with the people in Kilensari Village, Panarukan District, Situbondo Regency. Along with the times, the people of Kilensari Village began to be dynamic. This raises the question 1) What are the aspects that have experienced socio-cultural changes in the activities of the coastal community of Kilensari village? So, what are the factors driving this change? The research method used is descriptive qualitative. The location was chosen in Kilensari Village, Panarukan Subdistrict, Situbondo Regency because this location is the largest fishing village in Situbondo Regency and there is a 1000 km long monument on the north coast highway. The research subjects consisted of village heads, community leaders, wood crafts entrepreneurs. Data collection techniques in the form of observation, and in-depth interviews. The sampling technique is purposive sampling. Based on the results of the study, it can be seen that the aspects that experience changes in the management of wood crafts are aspects of knowledge, aspects of trust, aspects of socio-culture, and aspects of the economic system. While the factors that encourage change are contact with other cultures, people's dissatisfaction with certain areas of life, future orientation, and the value that humans must always try to improve their lives.Keywords: change, social, culture, woodworking.